Investigational multitargeted kinase inhibitors in development for head and neck neoplasms. (3rd April 2019) - Sola, Ana Marija; Johnson, Daniel E.; Grandis, Jennifer R.
ABSTRACT: Introduction : Despite advances in treatment, head and neck squamous cell carcinoma (HNSCC) survival rates remain stagnant. Current treatment is associated with significant toxicities and includes chemotherapy, radiation, surgery, and few targeted treatments. Targeted treatments, epidermal growth factor receptor (EGFR)-targeted agent, cetuximab, and immune checkpoint inhibitors, pembrolizumab and nivolumab, show improved toxicity profiles and modestly improved survival in select patients. An urgent need remains to identify novel targeted treatments for single-agent or combined therapy use. Areas covered : Multitargeted kinase inhibitors are small molecule inhibitors with limited toxicity. This review will focus on early-stage investigations of multitargeted tyrosine kinase inhibitors (m-TKIs) (those that target at least two tyrosine kinases) for HNSCC. Preclinical and early trials investigating m-TKIs for various disease settings of HNSCC will be evaluated for efficacy, identification of significant biomarkers and potential for combination therapy. Expert opinion : Few single agent m-TKIs have demonstrated efficacy in unselected HNSCC populations. The most promising clinical results have been obtained when m-TKIs are tested in combination with other therapies, including immunotherapy, or in mutation-defined subgroups of patients. The future success of m-TKIs will rely on identification, in preclinical models and clinical trials, of predictive biomarkers of response and mechanisms of innate and acquired resistance.